Solar Power Generation in Bangladesh: Status, Challenges and Measures - A K M Alamgir (IUBAT Review, 2024)
Efforts toward generation of electricity from solar source by various application technologies is now emerging in Bangladesh. To date, almost 3% of total electricity generation comes from various renewable resources, where 2% is contributed by solar power. Since inception of solar practice in mid 90’s, a collaborating effort by government and private organizations successfully set up a strong foundation of solar culture in the country being financially stimulated by the world donor agencies. In fact, the expectation of renewable sharing where solar is the major contributor is much higher in terms of near extinction of country’s fossil fuel, fore-coming energy demand and environmental concern. The status of current solar power production, existing challenges to be commensurate with national vision as well as global solar trend, and potential measures have been focused and analyzed in this review paper based on reported data and information. IUBAT Review—A Multidisciplinary Academic Journal, 7(1): 80-89